2022
DOI: 10.3390/biomedicines10102598
|View full text |Cite
|
Sign up to set email alerts
|

Cell Reprogramming for Regeneration and Repair of the Nervous System

Abstract: A persistent barrier to the cure and treatment of neurological diseases is the limited ability of the central and peripheral nervous systems to undergo neuroregeneration and repair. Recent efforts have turned to regeneration of various cell types through cellular reprogramming of native cells as a promising therapy to replenish lost or diminished cell populations in various neurological diseases. This review provides an in-depth analysis of the current viral vectors, genes of interest, and target cellular popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 157 publications
0
4
0
Order By: Relevance
“…19,20 The in vitro and in vivo generation of neurons via reprogramming of pluripotent stem cells has been demonstrated to be a rapid and efficient approach in terms of neuronal-related gene expression, morphology, connectivity, and electrophysiological properties. 21,22 In most of previously published in vitro reprogramming protocols, addition of glial cells to the culture was needed to obtain mature functional neurons. 19,23 However, in the absence of glia, Goparaju and collaborators found that transfection of human pluripotent stem cells with five mRNAs (encoding NGN1, NGN2, NGN3, ND1 and ND2) gives rise to neurons at day 7 of differentiation but only 50% of them showed 1 action potential 24 In contrast, already after 7 days and without the presence of glial cells, our protocol generates neurons with capacity to fire multiple (65% of the total) or at least one action potential (35%), making our protocol faster than the ones described to date.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The in vitro and in vivo generation of neurons via reprogramming of pluripotent stem cells has been demonstrated to be a rapid and efficient approach in terms of neuronal-related gene expression, morphology, connectivity, and electrophysiological properties. 21,22 In most of previously published in vitro reprogramming protocols, addition of glial cells to the culture was needed to obtain mature functional neurons. 19,23 However, in the absence of glia, Goparaju and collaborators found that transfection of human pluripotent stem cells with five mRNAs (encoding NGN1, NGN2, NGN3, ND1 and ND2) gives rise to neurons at day 7 of differentiation but only 50% of them showed 1 action potential 24 In contrast, already after 7 days and without the presence of glial cells, our protocol generates neurons with capacity to fire multiple (65% of the total) or at least one action potential (35%), making our protocol faster than the ones described to date.…”
Section: Discussionmentioning
confidence: 99%
“…Three approaches have arisen: recruitment of neural stem cell (NSC) niches to produce neurons, reprogramming of local glial cells into neurons, and transplantation of foetal progenitor cells. Various degrees of success have emerged from studies of cellular reprogramming in animal models of neurodegenerative diseases, recently extensively reviewed elsewhere [ 226 ]. Research in this field is emerging, and potentially contributing with new ways to restore CNS function and increase health span.…”
Section: Impact Of Rejuvenating Strategies In Brain Functionmentioning
confidence: 99%
“…Site-specific recombinase DNA enzyme called Cre, identifies the locations of 3 pairs of genes called loxp. The Cre enzyme mediates recombination, resulting in knocking out of the target genes between loxP sites (30,31).…”
Section: Cre-lox Systemmentioning
confidence: 99%